Experimental driving performance evaluation of battery-powered medium and heavy duty all-electric vehicles. (October 2022) - Sato, Susumu; Jiang, Yu Jade; Russell, Robert L.; Miller, J. Wayne; Karavalakis, Georgios; Durbin, Thomas D.; Johnson, Kent C.
Highlights: Heavy-duty battery-electric vehicles are a key to fully electrifying mobile sources. Actual performance data of heavy-duty battery electric vehicles is currently limited. The energy consumption rates for electric trucks were quantitatively evaluated. The energy consumption and regeneration were optimal during transient cycles. The electric vehicles have better fuel economy than conventional and hybrid vehicles. Abstract: As the push to reduce air pollutants and carbon dioxide for global warming continues, there is increasing interest in the development and deployment of battery electric vehicles for heavy-duty applications as one of the critical and challenging steps of a broader effort to fully electrify the transportation sector. This study evaluated and quantified the energy consumption rates and energy regeneration rates for three heavy-duty battery electric vehicles (a step van, a yard tractor, and a class 8 truck) using driving cycle tests with a heavy-duty vehicle chassis dynamometer. Information in this area is currently very limited, and yet it is critical to understanding how effective heavy-duty battery electric vehicles will be for a wide range of applications as the electrification of the heavy-duty vehicle market continues to expand. Energy consumption rates ranged from 0.37 and 2.71 kWh/km for most vehicle/cycle combinations. On a diesel liter energy-equivalent basis, the heavy-duty vehicles had approximately 3 to 6 times better energy consumption rates compared to comparable diesel vehicles, with weight normalized energy consumption rates also comparing favorably to the current and future greenhouse gas/fuel economy standards for equivalent diesel vehicles. Based on battery capacities ranging from 80 to 215 kWh, the vehicle ranges varied from 38.18 km to 171.2 km, with ranges of 115.9 km to 171.2 km for most types of driving and lower ranges of 38.18 to 42.20 km for sustained grade cycles. Overall, the advantage of improved energy consumption rates coupled with improvements that can be expected for battery technology and vehicle range, provide promise for expanded use of heavy-duty vehicles going into the future.